2011
DOI: 10.1590/s0100-29452011000200031
|View full text |Cite
|
Sign up to set email alerts
|

Uso de antibióticos para o controle de bactérias endógenas visando à micropropagação da figueira

Abstract: A descontaminação dos explantes é um dos princípios básicos para o sucesso da cultura de tecidos. Um dos problemas diagnosticados na propagação in vitro da figueira, através de gemas apicais, é a contaminação endógena dos explantes por bactérias. Este trabalho teve como objetivo avaliar a eficiência de alguns antibióticos em meio de cultura para o controle de bactérias endógenas em gemas apicais de figueira. Foram avaliados os seguintes tratamentos: T1(sem adição de antibiótico); T2 (30 mg L-1 de cloranfenicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
3
1
6
Order By: Relevance
“…In the present study, cultivar Ascolano 315 showed the highest bacterial contamination percentage for the WPM medium (Table 1). However, this percentage is lower than that found by Palu et al (2011), who obtained 39.14% of contamination by bacteria in fig tree apical buds, using cephalothin sodium antibiotics 150 mg.L -1 in a MS culture medium. Cultivars Arbequina and Ascolano 315 showed the highest means in the WPM medium.…”
Section: Resultscontrasting
confidence: 64%
“…In the present study, cultivar Ascolano 315 showed the highest bacterial contamination percentage for the WPM medium (Table 1). However, this percentage is lower than that found by Palu et al (2011), who obtained 39.14% of contamination by bacteria in fig tree apical buds, using cephalothin sodium antibiotics 150 mg.L -1 in a MS culture medium. Cultivars Arbequina and Ascolano 315 showed the highest means in the WPM medium.…”
Section: Resultscontrasting
confidence: 64%
“…Many authors have reported the use of antibiotics to control and/or eliminate microorganisms from in vitro cultures [13,44,45]. But depending on antibiotic concentration and the tolerance of the focal species, antibiotics may also have phytotoxic effects on the culture and alter in vitro plant growth [46,47].…”
Section: Survival Of Explantsmentioning
confidence: 99%
“…Microbial manifestation is one of the main causes of economic loss in commercial and scienti c laboratories devoted to tissue culture; therefore, controlling is essential for successful in vitro cultivation [12]. Accordingly, the prevention or elimination of microbial manifestation from in vitro cultivations has been the focus of several studies, ranging from the development of asepsis protocols and handling of mother plants, to the use of antimicrobial products in the culture medium [13].…”
Section: Introductionmentioning
confidence: 99%
“…Os desinfestantes superficiais como álcool ou hipoclorito de sódio muitas vezes podem controlar apenas os fungos, mas não garantem níveis aceitáveis de controle para bactérias, o que pode ser constatado por Vianna et al (2003), os quais utilizaram como descontaminante para os explantes de mamoeiro apenas hipoclorito de sódio em diferentes concentrações, sendo impossível conseguir explantes sem sinais visíveis de contaminação, principalmente por bactérias. Para o controle das bactérias, diversos autores citam a inclusão ao meio de cultura de antibióticos como ampicilina sódica, agrimicina, cloranfenicol, acido nalidíxico (Wilson & Power (1989), Garcia & Rafael (1990); Barros & Pasqual (1991), Leifert et al (1991), Pereira et al, (2010), Palu et al (2011). Também se pode adicionar os antibióticos ao meio de cultura por um período limitado, o necessário para a eliminação dos contaminantes (Kneifel & Leonhardt, 1992, Leifert et al, 1992 ou utilizá-los na forma de imersão antes do isolamento (Tanaka et al, 1983, Scortichini & Chiariotti, 1988.…”
Section: Palavrasunclassified